Management of Geriatric Acetabulum Fracture – A Case Report - R Ajay Nickson Samuel; K Tarun Prashanth; M R Thirunthaiyan; R Dorai Kumar; B Sundararaja (Journal of Orthopaedic Case Reports)
Introduction: Geriatric acetabular fractures resulting from low-energy trauma represent an emerging challenge in orthopedic trauma care. This case highlights the successful management of a complex osteoporotic acetabular fracture with medial dome impaction (“Gull sign”) and quadrilateral plate involvement using a modified Stoppa approach with suprapectineal plating, followed by an accelerated rehabilitation protocol. While not the first report of its kind, this case provides critical insights into achieving early weight-bearing in elderly patients, addressing a key gap in current management strategies for these challenging fractures. Case Report: A 63-year-old male presented with right hip pain and inability to bear weight after a standing-height fall. Imaging revealed a comminuted right acetabular fracture with superomedial dome impaction, quadrilateral plate involvement, and central subluxation. The patient underwent open reduction and internal fixation through a modified Stoppa approach using a suprapectineal plate. Postoperatively, an accelerated rehabilitation protocol was implemented, progressing to full weight-bearing by 6 weeks with radiographic evidence of union. Conclusion: This case demonstrates that anatomical reduction and stable fixation of complex geriatric acetabular fractures can be achieved through the modified Stoppa approach with suprapectineal plating. More importantly, it establishes the feasibility and safety of an accelerated rehabilitation protocol enabling full weight-bearing by 6 weeks postoperatively. These findings significantly advance the management of osteoporotic acetabular fractures by providing orthopedic surgeons with a replicable treatment strategy that prioritizes early mobilization – a critical factor in reducing complications and improving functional outcomes in elderly patients. The protocol presented here has broad clinical implications for geriatric trauma care and post-operative rehabilitation.